XFEM crack growth virtual monitoring in self-sensing CNT reinforced polymer nanocomposite plates using ANSYS. (15th March 2022) - Rodríguez-Tembleque, L.; Vargas, J.; García-Macías, E.; Buroni, F.C.; Sáez, A.
Abstract: This paper presents an eXtended Finite Element Method (XFEM)-based numerical scheme to compute electrical resistivity changes caused by the presence of cracks and the crack growth. Using the commercial finite element package ANSYS, the virtual continuous monitoring of the structure is solved in two steps. First, the strain response of the cracked composite domain is computed by means of the XFEM. In the second step, the electrical conductivity of the piezorresistive elements located in the domain are updated according to the strain state and the electric resistance between two electrodes of the damaged plate is computed. The comparison with the electric resistance measured for the undamaged plate allows us to detect the presence of a crack and its severity. Moreover, the crack growth process can be also monitored via the electric resistance increments. Several numerical studies are provided to show the capabilities of this computational framework. Highlights: Electro-mechanical computational framework for crack-growth simulation in CNTRC, using ANSYS. X-FEM addresses the mechanical behavior whilst piezoresistive the FE model the electrical behavior. Correlation study between crack growth and changes in the electrical resistance of the structure. Influence of crack-defects in the sensor performance. Virtual monitoring and sensing of structural integrity via piezoresistive nanocomposites.